Maker Cultures and the Prospects for Technological Action. - Nascimento, Susana; Pólvora, Alexandre (Science & Engineering Ethics, 2018)
Supported by easier and cheaper access to tools and expanding communities, maker cultures are pointing towards the ideas of (almost) everyone designing, creating, producing and distributing renewed, new and improved products, machines, things or artefacts. A careful analysis of the assumptions and challenges of maker cultures emphasizes the relevance of what may be called technological action, that is, active and critical interventions regarding the purposes and applications of technologies within ordinary lives, thus countering the deterministic trends of current directions of technology. In such transformative potential, we will explore a set of elements what is and could be technological action through snapshots of maker cultures based on the empirical research conducted in three particular contexts: the Fab Lab Network, Maker Media core outputs and initiatives such as Maker Faires, and the Open Source Hardware Association (OSHWA). Elements such as control and empowerment through material engagement, openness and sharing, and social, cultural, political and ethical values of the common good in topics such as diversity, sustainability and transparency, are critically analysed.